Associations between polychlorinated dibenzo-dioxins and polychlorinated dibenzo-furans exposure and oxidatively generated damage to DNA and lipid. (July 2019) - Zhang, Zhuang; He, Jintong; Shi, Tingming; Tang, Naijun; Zhang, Sukun; Wen, Sheng; Liu, Xiao; Zhao, Ming; Wang, Dongming; Chen, Weihong
Abstract: Polychlorinated dibenzo-dioxins and polychlorinated dibenzo-furans (PCDD/Fs) have been reported to induce reactive oxygen species and oxidative stress, but the dose-response relationships have not been explored in molecular epidemiological studies. In this study, a total of 602 participants were recruited, comprising of 215 foundry workers, 171 incineration workers and 216 residents living more than 5 km away from the plants as the reference group. Individual PCDD/Fs exposures were estimated according to PCDD/Fs levels of working and living ambient air and daily foods. Urinary 8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxodG) and 8-iso-prostaglandin-F2α (8-isoPGF2α) were determined to reflect oxidatively generated damage to DNA and lipid. Generalized linear models were used to access the associations between PCDD/Fs exposure and oxidative stress biomarkers. We found that PCDD/Fs exposure and urinary oxidative stress biomarkers of workers were all higher than those of the reference group. Significantly positive exposure-response relationships between individual PCDD/Fs exposures and urinary 8-oxodG and 8-iso-PGF2α were found. Each 1-unit increase in ln-transformed levels of PCDD/Fs exposure generated a 0.78 nmol/mmol creatinine increase in ln-transformed 8-oxodG and a 0.50 ng/mmol creatinine increase in ln-transformed 8-isoPGF2α in foundry workers, a 0.49 nmol/mmol creatinine increase in ln-transformed 8-oxodG and a 0.26 ng/mmol creatinine increase in ln-transformed 8-isoPGF2α in incineration workers, compared with the reference group. And such associations were not modified by tobacco use. Our findings could help to understand the dose-response relationships between PCDD/Fs and oxidatively generated damage to DNA and lipid, and provide an epidemiologic basis for conducting research on the carcinogenesis and other toxicity mechanisms of PCDD/Fs. Graphical abstract: Image 1 Highlights: PCDD/Fs levels were measured in both air and food samples. Individual PCDD/Fs exposure of workers and residents was estimated. Dose-response relationships between PCDD/Fs exposure and urinary 8-oxodG and 8-iso-PGF2α levels were explored in foundry and incineration workers respectively. PCDD/Fs exposure associated with oxidative stress levels in both smokers and nonsmokers.